Whose language counts? - Truan, Naomi (Enthalten in:European journal of applied linguistics;Berlin : de Gruyter, 2013-;12, Heft 1 (2024), 34-53 (gesamt 20);Online-Ressource)
Abstract: This position paper makes a critical intervention in one of the mostly salient sociolinguistic debates of the recent years, that of the integration of multilingual speakers in language ideological research. Although many scholars now recognize the need for decentering the ideal (ized) ‘monolingual native speakers’, they remain the default norm in language ideological research. Indeed, despite our efforts to dismantle our own language ideologies as linguists, the implicit focus on native speakers and monolinguals proceeds to the erasure or invisibilization (Irvine & Gal 2000) of multilinguals. Drawing on research on gender-inclusive language as well as my own empirical study on L2 speakers of German, I show why integrating a higher variety of language users is necessary—not only on ethical grounds, but also on theoretical ones. Altogether, this paper presents the challenges language ideological research still faces despite ongoing efforts to tackle multilingualism and offers possible solutions for language ideological research to become truly inclusive. Dieser theoretische Beitrag greift kritisch in eine der wichtigsten soziolinguistischen Debatten der letzten Jahre ein, nämlich die der Integration von mehrsprachigen Sprechenden in die sprachideologische Forschung. Obwohl viele Forschende inzwischen die Notwendigkeit erkannt haben, die Fixierung auf die*den ideale*n ‚einsprachige*n Muttersprachler*in‘ zu überwinden, bleiben monolinguale native speakers die Standardnorm in der sprachideologischen Forschung. Ich zeige, dass trotz unserer Bemühungen, unsere eigenen Sprachideologien als Linguist*innen abzubauen, der implizite Fokus auf Muttersprachler*innen und Einsprachige zur Löschung oder Unsichtbarmachung Mehrsprachiger führt (Irvine & Gal 2000). Am Beispiel der Forschung zur geschlechtergerechten Sprache erkläre ich, warum die Integration einer größeren Vielfalt von Sprechenden notwendig ist—und dies nicht nur aus ethischen, sondern auch aus theoretischen Gründen. Insgesamt stellt dieser Beitrag die Herausforderungen dar, denen sich die sprachideologische Forschung trotz laufender Bemühungen um die Mehrsprachigkeit noch immer gegenübersieht, und bietet mögliche Lösungen für eine wirklich inklusive sprachideologische Forschung. Este artículo realiza una contribución crítica a uno de los debates sociolingüísticos más destacados de los últimos años, a saber el de la integración de los hablantes multilingües en la investigación sobre ideologías lingüísticas. Aunque muchos estudiosos reconocen ahora la necesidad de descentrar al hablante nativo monolingüe “ideal”, este sigue siendo la norma por defecto en la investigación sobre ideologías lingüísticas. En este estudio se presenta la investigación sobre el lenguaje inclusivo de género como un ejemplo de cómo la investigación sobre ideologías lingüísticas sigue estando imbuida por las ideologías lingüísticas de los propios lingüistas sobre el hablante nativo y por el sesgo monolingüe, también enredada en construcciones ideológicas de “una lengua” perteneciente a “un estado”. Además, se sostiene en este artículo que, a pesar de nuestros esfuerzos por desmantelar como lingüistas nuestras propias ideologías lingüísticas, el enfoque implícito en los hablantes nativos y los monolingües procede al borrado o a la invisibilización (Irvine & Gal 2000) de hablantes multilingües. Tras haber identificado el problema, se muestra por qué es necesario integrar a una mayor variedad de usuarios de la lengua, no sólo por motivos éticos, sino también teóricos. En resumen, este artículo presenta los retos a los que todavía se enfrenta la investigación sobre ideologías lingüísticas a pesar de los esfuerzos que se están realizando para abordar el multilingüismo y ofrece posibles soluciones para que la investigación sobre ideologías lingüísticas sea realmente inclusiva. Cet article propose une intervention critique dans l’un des débats sociolinguistiques les plus importants de ces dernières années, à savoir l’intégration des locuteurs/-trices multilingues dans la recherche sur les idéologies langagières. Bien que de nombreux/-ses chercheurs/-ses reconnaissent aujourd’hui la nécessité de décentrer l’idéal du/de la locuteur/-trice natif/-ve monolingue, cette abstraction reste la norme par défaut dans la recherche sur les idéologies langagières. Je soutiens par ailleurs que malgré nos efforts pour démanteler nos propres idéologies linguistiques en tant que linguistes, l’accent implicite mis sur les locuteurs/-trices natifs/-ives et monolingues procède à une stratégie d’effacement ou d’invisibilisation des personnes multilingues (Irvine & Gal 2000). A partir de l’exemple de travaux récents sur l’écriture inclusive, je montre pourquoi l’intégration d’une plus grande variété de locuteurs/-trices est nécessaire, non seulement pour des raisons éthiques, mais aussi théoriques. Dans l’ensemble, cet article présente les défis auxquels la recherche sur les idéologies langagières est toujours confrontée malgré les efforts déployés pour s’attaquer au multilinguisme. Cette contribution propose enfin des solutions possibles pour que la recherche sur les idéologies langagières devienne véritablement inclusive.
10.1515/eujal-2024-0006
Keywords: kritische Soziolinguistik; Sprachideologien; Spracheinstellungen; Muttersprache; Monolingualismus; Mehrsprachigkeit; Erstsprache; Zweitsprache; Migration; Mobilität; critical sociolinguistics; language ideologies; language attitudes; native speaker; monolingual bias; multilingualism; first language; second language; migration; mobility